THU0567 Testing performance measures identifies gaps in juvenile idiopathic arthritis (JIA) care. (12th June 2018) - Barber, C.; Lacaille, D.; Lix, L.; Kroeker, K.; Marshall, D.A.; Shiff, N.
Abstract : Background: JIA is the most prevalent type of childhood inflammatory arthritis. Timely diagnosis, treatment and ongoing care by a paediatric rheumatologist are associated with improved outcomes. Objectives: To test the Arthritis Alliance of Canada's JIA Performance Measures: i) The percentage of patients with new onset JIA with at least one visit to a paediatric rheumatologist in the first year of diagnosis; ii) The percentage of patients with JIA under rheumatology care seen in follow-up by a paediatric rheumatologist at least once per year. Methods: Validated JIA case ascertainment algorithms were used to identify cases from provincial health administrative databases in Manitoba, Canada in patients<16 years of age with ≥6 months of health insurance coverage in the population registry between 01/04/2005 and 31/03/2015. Cases were identified by either 1 hospitalisation separation with an International Classification of Disease (ICD)−10 code for JIA (M05.X, M06.X, M08.X, M45.X) or ≥2 physician billing claims (ICD-9 codes: 714.x or 720.x) for JIA≥8 weeks apart within 2 years. A 3 year washout period prior to the first code was used to determine the percentage of incident JIA patients with ≥1 visit to a paediatric rheumatologist in the first year. For reporting the percentage of JIA patients seen in yearly follow-up, once a patient is seen at least twice by a paediatric rheumatologist they are considered under rheumatology care. The measure was computed by comparing yearly observed and expected follow-ups. The proportion of patients with gaps in care of >12 and>14 months between consecutive rheumatologist visits was also calculated. As there is no paediatric rheumatologist identifier in Manitoba administrative datasets, a physician was identified as a paediatric rheumatologist if they had ≥40 visits for individuals≤16 years in a year and at least 50% of those visits in a year were JIA. This identified 5 physicians. Results: 194 incident cases of JIA were diagnosed between 01/04/2008 and 03/31/2015. The median age at diagnosis was 9.1 years (Q1 5.5, Q3 12.8) and 71% were female. Table 1 describes the number of JIA cases who saw a paediatric rheumatologist within a year of diagnosis (between 51% and 81%). Table 2 describes the percentage of patients seen on a yearly basis with no significant changes seen over time (p=0.47). A single gap of >12 months was seen in 52% (n=144) and ≥2 gaps of >12 months were seen in 11% (n=28). One gap of >14 months was seen in 34% of cases, and only 5% had ≥2 gaps>14 months. Conclusions: Many JIA patients are not seen by a paediatric rheumatologist within a year of diagnosis, and up to half of those followed have at least 1 gap in care of >12 months. Such gaps may lead to a delay in diagnosis, timely treatment and ongoing care that could impact outcomes. Disclosure of Interest: None declared